Stems of Phragmites australis are buffering methane and carbon dioxide emissions - Dušek, Jiří; Faußer, Anna; Stellner, Stanislav; Kazda, Marian (The Science of the total environment, 2023)
Internal concentrations in the culm nodes of Phragmites australis and fluxes of methane (CH4) and carbon dioxide (CO2) were recorded in the treatment bed of constructed wetland (CW) with subsurface wastewater horizontal flow. Fluxes of CH4 and CO2 from the CW treatment bed were in ranges of 0 to 490 μmol m-2 h-1 and from 0 to 4499 μmol m-2 h-1 for CH4 and CO2, respectively. The highest CH4 soil fluxes were recorded in the unvegetated coarse gravel inflow zone of the CW treatment bed. The nearby inflow zone exhibited the highest CO2 fluxes. Internal culm node concentrations of CH4 and CO2 were related to oxygen (O2) stem concentrations and environmental conditions during diurnal courses. The concentrations of CH4 and CO2 gases were significantly correlated and opposing O2 concentrations. Culm node parameters and shoot density of P. australis influenced internal gas concentrations and the buffering of CH4 and CO2 emissions. The effect of buffering CH4 emissions is distinctive in the outflow zone of the treatment bed and is less important in the highly polluted inflow zone of the CW. Buffering of CH4 and partially also CO2 emissions by stems of P. australis is a process which affects the diurnal dynamics of CH4 and CO2 fluxes from common reed wetlands.
Keywords: Oxygen; Greenhouse gases; Methane; Root traits; Carbon dioxide; Common reed